2003
DOI: 10.1073/pnas.2133028100
|View full text |Cite|
|
Sign up to set email alerts
|

Conformation-dependent hydrophobic photolabeling of the nicotinic receptor: Electrophysiology-coordinated photochemistry and mass spectrometry

Abstract: We characterized the differential accessibility of the nicotinic acetylcholine receptor α1 subunit in the open, closed, and desensitized states by using electrophysiology-coordinated photolabeling by several lipophilic probes followed by mass spectrometric analysis. Voltage-clamped oocytes expressing receptors were preincubated with one of the lipophilic probes and were continually exposed to acetylcholine; UV irradiation was applied during 500-ms pulses to + 40 or to -140 mV (which produced closed or ≈50% ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 60 publications
5
48
1
Order By: Relevance
“…By contrast, loops 2 and 7 appear to be located within close proximity of the pre-TM1 region only in the presence of GABA, suggesting that these domains move relative to one another during the open or desensitized state. It is of interest to note that a recent study that examined state-selective incorporation of hydrophobic probes in the nAChR identified loop 7 of the nAChR ␣ 1 subunit as a region that undergoes a conformational change during receptor activation (32). Based on these results, we propose that there are intramolecular interactions between loop 7 and the pre-TM1 region that are important for receptor activation.…”
Section: Double Mutant Experiments Reveal Asp 146 -Lys 215mentioning
confidence: 77%
“…By contrast, loops 2 and 7 appear to be located within close proximity of the pre-TM1 region only in the presence of GABA, suggesting that these domains move relative to one another during the open or desensitized state. It is of interest to note that a recent study that examined state-selective incorporation of hydrophobic probes in the nAChR identified loop 7 of the nAChR ␣ 1 subunit as a region that undergoes a conformational change during receptor activation (32). Based on these results, we propose that there are intramolecular interactions between loop 7 and the pre-TM1 region that are important for receptor activation.…”
Section: Double Mutant Experiments Reveal Asp 146 -Lys 215mentioning
confidence: 77%
“…The conformational change of loop F during channel activation is further supported by increased photolabeling of loop F in the α1 subunit of nAChR in the open state, although the direction of the movement is not completely clear [53] . Mutation of a loop F residue (εD175N) of nAChR clearly influences channel gating, suggesting the importance of the loop F in channel activation [54] .…”
Section: Activation Mechanismmentioning
confidence: 99%
“…Numerous MS-based covalent labeling experiments have been conducted on membrane proteins [28,29], e.g., for topologic investigations [30], as well as for monitoring conformational changes [29,[31][32][33][34] and binding interactions [35][36][37].…”
mentioning
confidence: 99%